Investigating the synergistic antioxidant effects of some flavonoid and phenolic compounds - H. Hajimehdipoor; R. Shahrestani; M. Shekarchi (Iranian Society of Pharmacognosy, 2014)
Phenolic and flavonoid compounds are secondary metabolites of plants which possess various activities such as anti-inflammatory, analgesic, anti-diabetes and anticancer effects. It has been established that these compounds can scavenge free radicals produced in the body. Because of this ability, not only the plants containing phenolic and flavonoid compounds but also, the pure compounds are used in medicinal products for prevention and treatment of many disorders. Considering that the golden aim of the pharmaceutical industries is using the most effective compounds with lower concentrations, determination of the best combination of the compounds with synergistic effects is important. In the present study, synergistic antioxidant effects of four phenolic compounds including caffeic acid, gallic acid, rosmarinic acid, chlorogenic acid and two flavonoids,  rutin and quercetin, have been investigated by FRAP (Ferric Reducing Antioxidant Power) method. The synergistic effect was assessed by comparing the experimental antioxidant activity of the mixtures with calculated theoretical values and the interactions of the compounds were determined. The results showed that combination of gallic acid and caffeic acid demonstrated considerable synergistic effects (137.8%) while other combinations were less potent. Among examined substances, rutin was the only one which had no effect on the other compounds. The results of ternary combinations of compounds demonstrated antagonistic effects in some cases. This was more considerable in mixture of rutin, caffeic acid, rosmarinic acid (-21.8%), chlorogenic acid, caffeic acid, rosmarinic acid (-20%), rutin, rosmarinic acid, gallic acid (-18.5%) and rutin, chlorogenic acid, caffeic acid (-15.8%), while, combination of quercetin, gallic acid, caffeic acid (59.4%) and quercetin, gallic acid, rutin (55.2%) showed the most synergistic effects. It was concluded that binary and ternary combination of quercetin, rutin, caffeic acid, chlorogenic acid, gallic acid and rosmarinic acid could influence the antioxidant ability; therefore, to obtain the best antioxidant effects in products containing these materials, the interactions should be mentioned.